$(δ, γ)$-Dunkl Lipschitz functions in the space $L^{2}(\mathbb{R}, |x|^{2α+1}dx)$ - El Hamma, M.; Lahlali, H.; Daher, R. (Carpathian Mathematical Publications, 2014)
Using a generalized Dunkl translation, we obtain an analog of Theorem 5.2 in Younis' paper [2] for the Dunkl transform for functions satisfying the $(δ, γ)$-Dunkl Lipschitz condition in the space $L^{2}(\mathbb{R}, |x|^{2α+1}dx)$.}